REHABILITATION OF ELDERLY AND ELDERLY PATIENTS IN THE CONDITIONS OF SANATORIUM-RESORT INSTITUTIONS (Modern education and development, 2025)
According to numerous literary sources, it is known that the adaptive capabilities of an aging organism are reduced, and the likelihood of developing various diseases is higher. In this regard, the role of sanogenetic mechanisms, their stimulation and maintenance, is especially important in the case of the development of diseases in elderly and elderly patients.